HIGH SCHOOL ENGLISH TEACHERS' ICT LITERACY IN TEACHING ENGLISH - Gayuh Adi Prayoga; Y.G. Harto Pramono (Magister Scientiae, 2021)
This study was aimed to investigate high school English teachers’ ICT literacy with the following more specific objectives: (i) to figure out how well of high school English teachers were familiar with various types of ICT for educational purposes; (ii) to figure out the extent to which English teachers implement ICT in their teaching; (iii) to figure out the obstacles English teachers had in implementing their knowledge of ICT in their teaching. Generation Z or gen Z are those who were born in digital era and are exposed to technology since from their young age. To teach this generation, teachers need to be literate to technology and should master certain knowledge that enables them to integrate technology in their teaching. Quantitative decriptive research design was employed in this study. A set of five point Likert scale questionnaire was distributed to English teachers who taught in Junior and Senior high schools in Surabaya and was analyzed using descriptive statistics. The findings indicated that majority of the respondents’ familiarity with the types of hardware and software was ranging from quite well to very well; the majority of the respondents’ frequency in using ICT was very often; and the only obstacle the teachers faced was lack of effective training to implement ICT in teaching. The present study may give insights for teacher development programs to improve their proficiency in implementing ICT in their classes to teach generation Z.